Purification, cloning, expression and immunological analysis of Scylla serrata arginine kinase, the crab allergen - Shen, Yuan; Cao, Min-Jie; Cai, Qiu-Feng; Su, Wen-Jin; Yu, Hui-Lin; Ruan, Wei-Wei; Liu, Guang-Ming (Journal of the science of food and agriculture, 2011)
BACKGROUND: Although crustaceans have been reported to be one of the most common causes of IgE‐mediated allergic reactions, there are no reports about the characterization and identification of arginine kinase (AK) from the mud crab (Scylla serrata) as allergen. In the present study, the purification, molecular cloning, expression and immunological analyses of the IgE allergen AK from the mud crab were investigated. RESULTS: The results showed that cloned DNA fragments of AK from the mud crab had open reading frames of 1021 bp, predicted to encode proteins with 356 amino acid residues. Sequence alignment revealed that mud crab AK shares high homology with other crustacean species. Mud crab AK gene was further recombined with the vector of pGEX‐4T‐3 and expressed in Escherichia coli BL 21. 2‐D electrophoresis suggested that native AK (nAK) and recombinant AK (rAK) shared the same molecular weight of 40 kDa, and the pI is 6.5 and 6.3, respectively. The nAK and rAK were further confirmed by matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry. Immunoblotting analysis and colloidal gold immunochromatographic assay (GICA) using sera from subjects with crustacean allergy confirmed that the nAK and rAK reacted positively with these sera, indicating AK is a specific allergen of mud crab. CONCLUSION: Both of purified nAK and rAK reacted positively with sera from subjects with crustacean allergy in immunoblotting and GICA analysis, indicating AK is a common allergen of mud crab. In vitro expressed AK is proposed as a source of the protein for immunological or clinical studies. Copyright © 2011 Society of Chemical Industry